Electronic Trial At The Supreme Court: Needs, Challenges And Arrangement - Nurjihad Nurjihad; Ariyanto Ariyanto (Muhammadiyah University Press, 2021)
Purpose of thestudy: This study aims to find out about the current needs, challenges, and arragment for The Electronic Trial at The Supreme Courts. The implementation of e-court that has been running so far still causes problems, so it needs an in-depth study.Methodology: In this research, the method used was normative juridical using a statutory and conceptual approach.Results: The result of this study conclude that: first, the factual needs of the implementation of electronic trials in Indonesia cannot be separated from the social transformation that occurs in Indonesian society itself. Second, the general challenge in the implementation of electronic trials, which are trials and verdicts pronounced in court hearings that are open to the public or in public, is one part that is inseparable from the principle of fair trial. Third, the regulations related to the public trial should start from the preparation of PERMA that must obey the principle and with laws that are hierarchically higher than PERMA.Applications of this study: This research is expected to identify the challenges posed in electronic courts, and provide policy recommendations on the regulation of electronic courts in Indonesia.Novelty/ Orginalty of this study: Changes to the Law on Judicial Power must be formulated first in order to facilitate electronic court process services in the current digital era. Then, the existing PERMA needs to be adjusted to the principles of the principle of a trial open to the public in order to prevent conflicts with the laws and regulations on it.